Nationalism In The Indonesian Multicultural Community - Yuliani Sri Widaningsih (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Indonesia's historical experience with nationalism, especially in relation to ethnicity andreligion is very complex. The complexity was not only due to differences in historicalexperiences in the process of growing nationalism, but also by the reality of Indonesiawhich is very pluralistic, either ethnically or religion. Indonesian ethnographic map isvery complex, it is as a result of the region's typography. Indonesia populated by largenumbers of ethnic group which having physical -biological and cultural similaritiessubstantially.Keywords: Nasionalism, Indonesian, Multiculural Community